PENGARUH MOTIVASI PADA MINAT MAHASISWA NON AKUNTANSI UNTUK MENGIKUTI PENDIDIKAN PROFESI AKUNTANSI - Dyastari, Ni Putu Sumi; Yadnyana, I Ketut (E-Jurnal Akuntansi, 2016)
This study aimed to examine the effect of motivation on student interest in non-accounting for follow PPAk. This research was conducted at the Faculty of Economics and Business, University of Udayana in non-accounting students regular forces S1 2012. The sampling method this research is non probability sampling method with saturated sampling technique. Data were collected using a questionnaire survey techniques. Respondents of this study as many as 185 people. Model analysis of the data used is multiple linear regression. Results of studies have shown that the variable analysis of social motivation, motivation quality, career motivation, economic motivation positive effect on the interest of non-accounting students to attend Professional Accounting Education (PPAk). This suggests that non-accounting  students at the Faculty of Economics and Business, University of Udayana assume Professional Accounting Education is an education that can increase student knowledge in the field of accounting so that it can become a professional accountant.
Keywords: Social Motivation, Quality Motivation, Career Motivation, Economics Motivation, Interests Following PPAk